Central fatigue after cycling evaluated using peripheral magnetic stimulation - Kremenic, I. J.; Glace, B. W.; Ben-Avi, S. S.; Nicholas, S. J.; McHugh, M. P. (Medicine & Science in Sports & Exercise, 2009)
Central and peripheral mechanisms contribute to fatigue during exercise. Electrical and transcranial magnetic stimulation have been used to assess these fatigue mechanisms. Peripheral magnetic stimulation (PMS) of the femoral nerve is associated with very little subject discomfort and has been shown to elicit quadriceps contractions of >70% maximal voluntary contraction (MVC).